2015
DOI: 10.1073/pnas.1511167112
|View full text |Cite
|
Sign up to set email alerts
|

Structures of two bacterial resistance factors mediating tRNA-dependent aminoacylation of phosphatidylglycerol with lysine or alanine

Abstract: The cytoplasmic membrane is probably the most important physical barrier between microbes and the surrounding habitat. Aminoacylation of the polar head group of the phospholipid phosphatidylglycerol (PG) catalyzed by Ala-tRNA Ala -dependent alanyl-phosphatidylglycerol synthase (A-PGS) or by Lys-tRNA Lys -dependent lysyl-phosphatidylglycerol synthase (L-PGS) enables bacteria to cope with cationic peptides that are harmful to the integrity of the cell membrane. Accordingly, these synthases also have been designa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 47 publications
1
64
0
Order By: Relevance
“…38 Several studies have tried to determine the phenotypical changes correlated with synthesis of Lys-PG compared with Ala-PG in S. aureus and P. aeruginosa . 24,30 These investigations showed that substitution of Lys-PG (which confers a net charge of +1) with Ala-PG (which bears a neutral net charge) did not affect bacterial susceptibility to CAMPs such as nisin and gallidermin, or to the CAMP-like antibiotic daptomycin. These findings suggest that the α amino group of the aa moiety of aa-PG alone is able to enhance antimicrobial resistance in bacteria.…”
Section: Aapgs Mediated Lipid Remodeling Uses Several Aa-trnas As Submentioning
confidence: 99%
See 2 more Smart Citations
“…38 Several studies have tried to determine the phenotypical changes correlated with synthesis of Lys-PG compared with Ala-PG in S. aureus and P. aeruginosa . 24,30 These investigations showed that substitution of Lys-PG (which confers a net charge of +1) with Ala-PG (which bears a neutral net charge) did not affect bacterial susceptibility to CAMPs such as nisin and gallidermin, or to the CAMP-like antibiotic daptomycin. These findings suggest that the α amino group of the aa moiety of aa-PG alone is able to enhance antimicrobial resistance in bacteria.…”
Section: Aapgs Mediated Lipid Remodeling Uses Several Aa-trnas As Submentioning
confidence: 99%
“…Several enzymes with altered aa-tRNA and lipid substrate specificities have been identified, and the recently solved crystal structures of two aaPGSs have shed light on the molecular mechanism of tRNA-dependent systems for lipid aminoacylation. 30 …”
Section: Trna-dependent Aminoacylation Of Membrane Phosphatidylglycerolmentioning
confidence: 99%
See 1 more Smart Citation
“…The pivotal protein for aminoacyl-PG biosynthesis from L-aminoacyl-tRNA and PG is the lysyl-PG synthase MprF (multiple peptide resistance factor) 8 which appears to have a broad range of specificity for L-aminoacyl-tRNAs 9, 10 . The crystal structures of the cytoplasmic catalytic domains of two MprFs, with one specific for lysyl- the other for alanyl-PG biosynthesis, have recently been elucidated 11 . The catalytic domains of the two MprF enzymes have a long tunnel for accommodating PG with the catalytic site located at the narrowest part of the tunnel 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structures of the cytoplasmic catalytic domains of two MprFs, with one specific for lysyl- the other for alanyl-PG biosynthesis, have recently been elucidated 11 . The catalytic domains of the two MprF enzymes have a long tunnel for accommodating PG with the catalytic site located at the narrowest part of the tunnel 11 . The primary and tertiary structures of MprF resemble that of FemX which catalyzes L-alanyl transfer from tRNA to a peptidoglycan precursor 12 .…”
Section: Introductionmentioning
confidence: 99%